2022
DOI: 10.1093/jjco/hyac099
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic role of deferred cytoreductive nephrectomy in patients with metastatic renal cell carcinoma treated with nivolumab plus ipilimumab

Abstract: Objectives To explore the therapeutic role of deferred cytoreductive nephrectomy in patients with metastatic renal cell carcinoma treated with nivolumab plus ipilimumab. Patients and methods Forty-one patients with synchronous metastatic renal cell carcinoma who received nivolumab plus ipilimumab as first-line systemic therapy at our affiliated institutions were retrospectively evaluated. We focused on the prognosis, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In the sample size > 400 subgroup, the CN group had significantly lower risk of death compared to the No CN group (HR = 0.52, 95% CI 0.32–0.84, p = 0.007, I 2 = 83%) ( 21 23 ). Additionally, for the subgroup with a sample size ≤ 400, the CN group was correlated with better OS than for the No CN group (HR = 0.53, 95% CI 0.35–0.80, p = 0.002, I 2 = 87%) ( Figure 5 ) ( 4 , 5 , 24 26 ). In the subgroup analysis of the ICIs as first-line therapy, the CN group had significantly lower risk of death compared to the No CN group (HR = 0.50, 95% CI 0.27–0.92, p = 0.03, I 2 = 83%) ( 21 , 22 , 24 ).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…In the sample size > 400 subgroup, the CN group had significantly lower risk of death compared to the No CN group (HR = 0.52, 95% CI 0.32–0.84, p = 0.007, I 2 = 83%) ( 21 23 ). Additionally, for the subgroup with a sample size ≤ 400, the CN group was correlated with better OS than for the No CN group (HR = 0.53, 95% CI 0.35–0.80, p = 0.002, I 2 = 87%) ( Figure 5 ) ( 4 , 5 , 24 26 ). In the subgroup analysis of the ICIs as first-line therapy, the CN group had significantly lower risk of death compared to the No CN group (HR = 0.50, 95% CI 0.27–0.92, p = 0.03, I 2 = 83%) ( 21 , 22 , 24 ).…”
Section: Resultsmentioning
confidence: 98%
“…In the studies included, three studies compared the outcomes of deferred versus upfront CN in selected patients. Two studies reported that deferred CN did not lead to a superior OS than upfront CN in patients (21, 26), while one study suggested that OS rate tended to be higher with deferred CN in comparison to upfront CN (24). Ghatalia et al (30) also demonstrated that no statistically significant difference in OS was observed between the upfront and deferred groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reports of pCR in the primary lesion in patients who underwent nephrectomy after first‐line immunotherapy‐based combination regimens are increasing. As shown in Table 2, 11–16 pCR with these novel therapies has been reported in 5.3–30% of patients. However, most of the reports are for ipilimumab plus nivolumab therapy, and the pCR rates for immunotherapy plus TKI are unclear.…”
Section: Discussionmentioning
confidence: 94%